Long non-coding RNA AGAP2-AS1, functioning as a competitive endogenous RNA, upregulates ANXA11 expression by sponging miR-16-5p and promotes proliferation and metastasis in hepatocellular carcinoma - Zhikui Liu (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Accumulating evidence has highlighted the potential role of long non-coding RNAs (lncRNAs) in the biological behaviors of hepatocellular carcinoma (HCC). Here, we elucidated the function and possible molecular mechanisms of the effect of lncRNA-AGAP2-AS1 on the biological behaviors of HCC. Methods EdU, Transwell and flow cytometry were used to determine proliferation, migration, invasion and apoptosis of HCC cells in vitro. The subcutaneous tumor model and lung metastasis mouse model in nude mice was established to detect tumor growth and metastasis of HCC in vivo. The direct binding of miR-16-5p to 3’UTR of ANXA11 was confirmed by luciferase reporter assay. The expression of AGAP2-AS1 and miR-16-5p in HCC specimens and cell lines were detected by real-time PCR. The correlation among AGAP2-AS1 and miR-16-5p were disclosed by a dual-luciferase reporter assay, RIP assay and biotin pull-down assay. Results Here, we demonstrated that AGAP2-AS1 expression was up-regulated in HCC tissues and cell lines, especially in metastatic and recurrent cases. Gain- and loss-of-function experiments indicated that AGAP2-AS1 promoted cell proliferation, migration, invasion, EMT progression and inhibited apoptosis of HCC cells in vitro and in vivo. Further studies demonstrated that AGAP2-AS1 could function as a competing endogenous RNA (ceRNA) by sponging miR-16-5p in HCC cells. Functionally, gain- and loss-of-function studies showed that miR-16-5p promoted HCC progression and alteration of miR-16-5p abolished the promotive effects of AGAP2-AS1 on HCC cells. Moreover, ANXA11 was identified as direct downstream targets of miR-16-5p in HCC cells, and mediated the functional effects of miR-16-5p and AGAP2-AS1 in HCC, resulting in AKT signaling activation. Clinically, AGAP2-AS1 and miR-16-5p expression were markedly correlated with adverse clinical features and poor prognosis of HCC patients. We showed that hypoxia was responsible for the overexpression of AGAP2-AS1 in HCC. And the promoting effects of hypoxia on metastasis and EMT of HCC cells were reversed by AGAP2-AS1 knockdown. Conclusions Taken together, this research supports the first evidence that AGAP2-AS1 plays an oncogenic role in HCC via AGAP2-AS1/miR-16-5p/ANXA11/AKT axis pathway and represents a promising therapeutic strategy for HCC patients.